Identification of MHC Haplotypes Associated with Drug-induced Hypersensitivity Reactions in Cynomolgus Monkeys. (January 2017) - Wu, Hong; Whritenour, Jessica; Sanford, Jonathan C.; Houle, Christopher; Adkins, Karissa K.
Drug-induced hypersensitivity reactions can significantly impact drug development and use. Studies to understand risk factors for drug-induced hypersensitivity reactions have identified genetic association with specific human leukocyte antigen (HLA) alleles. Interestingly, drug-induced hypersensitivity reactions can occur in nonhuman primates; however, association between drug-induced hypersensitivity reactions and major histocompatibility complex (MHC) alleles has not been described. In this study, tissue samples were collected from 62 cynomolgus monkeys from preclinical studies in which 9 animals had evidence of drug-induced hypersensitivity reactions. Microsatellite analysis was used to determine MHC haplotypes for each animal. A total of 7 haplotypes and recombinant MHC haplotypes were observed, with distribution frequency comparable to known MHC I allele frequency in cynomolgus monkeys. Genetic association analysis identified alleles from the M3 haplotype of the MHC I B region (B*011:01, B*075:01, B*079:01, B*070:02, B*098:05, and B*165:01) to be significantly associated (χ 2 test for trend, p < 0.05) with occurrence of drug-induced hypersensitivity reactions. Sequence similarity from alignment of alleles in the M3 haplotype B region and HLA alleles associated with drug-induced hypersensitivity reactions in humans was 86% to 93%. These data demonstrate that MHC alleles in cynomolgus monkeys are associated with drug-induced hypersensitivity reactions, similar to HLA alleles in humans.